Early T-cell responses to dengue virus epitopes in Vietnamese adults with secondary dengue virus infections - Simmons, Cameron (2018)
T-cell responses to dengue viruses may be important in both protective immunity and pathogenesis. This study of 48 Vietnamese adults with secondary dengue virus infections defined the breadth and magnitude of peripheral T-cell responses to 260 overlapping peptide antigens derived from a dengue virus serotype 2 (DV2) isolate. Forty-seven different peptides evoked significant gamma interferon enzyme-linked immunospot (ELISPOT) assay responses in 39 patients; of these, 34 peptides contained potentially novel T-cell epitopes. NS3 and particularly NS3200-324 were important T-cell targets. The breadth and magnitude of ELISPOT responses to DV2 peptides were independent of the infecting dengue virus serotype, suggesting that cross-reactive T cells dominate the acute response during secondary infection. Acute ELISPOT responses were weakly correlated with the extent of hemoconcentration in individual patients but not with the nadir of thrombocytopenia or overall clinical disease grade. NS3556-564 and Env414-422 were identified as novel HLA-A*24 and B*07-restricted CD8+ T-cell epitopes, respectively. Acute T-cell responses to natural variants of Env414-422 and NS3556-564 were largely cross-reactive and peaked during disease convalescence. The results highlight the importance of NS3 and cross-reactive T cells during acute secondary infection but suggest that the overall breadth and magnitude of the T-cell response is not significantly related to clinical disease grade.